Vertical Distribution and Controls on Heavy Metal(loid)s in Shallow Fissure Soils of Karst Geochemical Background Regions - Liang Tai; Yong Niu; Jia Chen; Gang Li; Pingping Fan; Feng Zhang; Tingjun Tan; Kaiqian Shi (Water, Air, & Soil Pollution, 2026)

Stroke Mechanisms in Intracranial Atherosclerotic Disease: A Modified Classification System and Clinical Implications - Shuang Li; Xuan Tian; Xueyan Feng; Bonaventure Ip; Hing Lung Ip; Jill Abrigo; Lina Zheng; Yuying Liu; Yu Liu; Ziqi Li; Tingjun Liang; Karen K. Y. Ma; et al. (Translational Stroke Research, 2025)
Background In patients with symptomatic intracranial atherosclerotic stenosis (sICAS), recent evidence has suggested an association between artery-to-artery embolism (AAE) and cortical borderzone (CBZ) infarcts. Methods We recruited patients with 50–99% anterior-circulation sICAS in this cohort. Stroke mechanisms were categorized as isolated parent artery atherosclerosis occluding penetrating artery (PAO), isolated AAE, isolated hypoperfusion, and mixed mechanisms, using two classification systems. In Classification I, the probable stroke mechanisms of internal borderzone and CBZ infarcts were both hypoperfusion, which were respectively hypoperfusion and AAE in Classification II. Other classification criteria were the same. We investigated and compared the predictive values of the two systems in predicting 90-day and 1-year recurrent ischemic stroke in the same territory (SIT). Results Among 145 patients (median age 62 years), 101 (69.7%) were males. We found significant difference in the proportions of baseline stroke mechanisms between these two systems (p < 0.001). Eleven (7.6%) and 19 (13.1%) patients respectively had 90-day or 1-year recurrent SIT. Classification II better predicted the risk of 90-day recurrent SIT than Classification I, when patients were divided into 4 groups according to baseline stroke mechanisms (p = 0.029), or by the presence of hypoperfusion (p < 0.001). The two classification systems had comparable predictive values for 1-year recurrent SIT. Conclusions In medically treated sICAS patients, considering AAE rather than hypoperfusion as the stroke mechanism for CBZ infarcts could better predict early recurrent SITs.

Pilot-scale application of sludge fermentation-driven nitrogen removal process with rapid in-situ enrichment of anammox bacteria for sustainable treatment of municipal wastewater and excess sludge - Shiwei Hao; Li Zhang; Jingfeng Gao; Xuepeng Fan; Tingjun Dong; Jiachun Yang; Shuang Lan; Yongzhen Peng (Chemical Engineering Journal, 2025)

Time-Series models for ground subsidence and heave over permafrost in InSAR Processing: A comprehensive assessment and new improvement - Chengyan Fan; Cuicui Mu; Lin Liu; Tingjun Zhang; Shichao Jia; Shengdi Wang; Wen Sun; Zhuoyi Zhao (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Distribution mechanisms of soil surface erosion and underground leakage in karst areas of China: A systematic, quantitative review - Jia Chen; Pingping Fan; Feng Zhang; Tingjun Tan; Nufang Fang; Zeyan Wu; Zhongwu Li; Yaojun Liu (CATENA, 2024)

Enhancing shrimp growth and immunity with green algal Caulerpa lentillifera polysaccharides through gut microbiota regulation - Yanmei Tong; Qiangyong Li; Chunling Yang; Min Peng; Xiuli Chen; Qiang Liu; Yuliu Huang; Pengfei Feng; Digang Zeng; Fan Wang; Tingjun Hu; Qingyun Liu; et al. (Algal Research, 2024)

Efficient photocatalytic reduction of nitrate byproducts during anammox process by novel extracellular polymeric substances-embedded NH2-MIL-101(Fe) photocatalysts - Li Zhang; Running Fan; Tingjun Dong; Quanhao Dou; Yongzhen Peng; Shou-Qing Ni; Jiachun Yang (Bioresource Technology, 2024)

Degradation properties of fulvic acid and its microbially driven mechanism from a partial nitritation bioreactor through multi-spectral and bioinformatic analysis - Quanhao Dou; Li Zhang; Tingjun Dong; Zixuan Song; Xuepeng Fan; Yongzhen Peng; Xiayan Wang; Jiachun Yang (Journal of Environmental Sciences, 2024)

How tax competition affects China’s environmental pollution?: A spatial econometric analysis - Kunming Li; Jianhua Wen; Tingjun Jiang; Xiamin Fan; Linxing Huang (Environment, Development and Sustainability, 2023)

Mitigating mechanism of nZVI-C on the inhibition of anammox consortia under long-term tetracycline hydrochloride stress: Extracellular polymeric substance properties and microbial community evolution - Li Zhang; Zixuan Song; Tingjun Dong; Xuepeng Fan; Yongzhen Peng; Jiachun Yang (Journal of Hazardous Materials, 2023)

Acceleration of thaw slump during 1997–2017 in the Qilian Mountains of the northern Qinghai-Tibetan plateau - Cuicui Mu; Jianguo Shang; Tingjun Zhang; Chengyan Fan; Shufa Wang; Xiaoqing Peng; Wen Zhong; Feng Zhang; Mei Mu; Lin Jia (Landslides, 2020)

Establishment and characterization of a new marine fish cell line from ovary of barfin flounder (Verasper moseri) - Xiaohui Xu; Tingjun Fan; Guojian Jiang; Xiuxia Yang (Journal of Ocean University of China, 2015)

Development of an inactivated iridovirus vaccine against turbot viral reddish body syndrome - Tingjun Fan; Xiuzhong Hu; Liyan Wang; Xiaofen Geng; Guojian Jiang; Xiuxia Yang; Miaomiao Yu (Journal of Ocean University of China, 2012)

Establishment of a spleen cell line from large yellow croaker Pseudosciaena crocea and its primitive application in foreign gene transfection - Ai Sun; Tingjun Fan; Xiuxia Yang; Bin Xu; Xiaohui Xu; Xueyang Guo (Journal of Ocean University of China, 2011)

Patterns and cellular mechanisms of arm regeneration in adult starfish Asterias rollestoni bell - Tingjun Fan; Xianyuan Fan; Yutang Du; Wenjie Sun; Shaofeng Zhang; Jiaxin Li (Journal of Ocean University of China, 2011)

Development of 57 novel polymorphic microsatellite markers in half-smooth tongue sole (Cynoglossus semilaevis) - Guidong Miao; Ying Xu; Di Wang; Songlin Chen; Tingjun Fan; Yongsheng Tian (Journal of Ocean University of China, 2011)

Comparative studies on sorting cells from Artemia sinica at different developmental stages for in vitro cell culture - Guojian Jiang; Xiaohui Xu; Yi Jing; Ruixin Wang; Tingjun Fan (In Vitro Cellular & Developmental Biology - Animal, 2011)

Establishment and characterization of a new cell line from the kidney of spotted halibut Verasper variegates - Xianli Wang; Songlin Chen; Zhenxia Sha; Tingjun Fan; Na Wang (Journal of Ocean University of China, 2010)

Effects of several immunostimulants on phenoloxidase and hemocytes of the crab Charybdis japonica - Tingjun Fan; Miaomiao Yu; Lingling Yang; Zhenping Shi; Wenjie Sun; Rishan Cong; Xiuxia Yang; Guojian Jiang (Journal of Ocean University of China, 2009)

Cloning and Expression of lipP, A Gene Encoding a Cold-Adapted Lipase from Moritella sp.2-5-10-1 - Xiuxia Yang; Xuezheng Lin; Tingjun Fan; Ji Bian; Xiaohang Huang (Current Microbiology, 2008)

Observations on the treatment of natural haemosporidia infections by total alkaloid ofPeganum harmala L. in cattle - Tingjun Hu; Bingtang Fan; Jilan Liang; Sixi Zhao; Ping Dang; Fang Gao; Mingxian Dong (Tropical Animal Health and Production, 1997)

Effect of total alkaloid ofPeganum harmala L. in the treatment of experimental haemosporidian infections in cattle - Bingtang Fan; Jilan Liang; Jucheng Men; Fang Gao; Guangling Li; Sixi Zhao; Tingjun Hu; Ping Dang; Ling Zhang (Tropical Animal Health and Production, 1997)